Impacto de las importaciones por uso o destino económico en el Producto Bruto Interno de la región Loreto, periodo 2014 - 2018 - Ruiz Vasquez de Cuadros, Yolanda Maribel (2021)
According to economic theory, imports are inversely related to the Gross Domestic Product. The objective of this thesis was to determine the impact of imports by economic use or destination on the Gross Domestic Product of the Loreto region, in the period 2014 - 2018. For this, this Quantitative, Correlational and level research was carried out. Non-Experimental design. The investigation concludes that there is no relationship between imports and the Gross Domestic Product, having obtained a Correlation Coefficient that was r = -0.346387786, a value below -0.75. Similarly, the Coefficient of Determination was R2 = 0.119984499; very far from 1; which shows that there is no statistical significance between the variables. Likewise, imports of goods had a variable behavior, having accumulated a reduction of -38.93% from 2014 to 2018. The analysis of imports by item reveals that the importation of Capital Goods occupies the first place, as it represents 68.13% of total purchases from abroad, mainly due to the acquisitions of goods for the industry, dedicated in greater proportion to oil activity. On the other hand, the analysis of the contribution of economic activities to the formation of the Gross Domestic Product shows that the Exploitation of Oil, Gas and Minerals occupies the first place with 18.66%.